2014
DOI: 10.1111/j.1600-0706.2013.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Bottom–up regulates top–down: the effects of hybridization of grass endophytes on an aphid herbivore and its generalist predator

Abstract: The ecological consequences of hybridization of microbial symbionts are largely unknown. We tested the hypothesis that hybridization of microbial symbionts of plants can negatively affect performance of herbivores and their natural enemies. In addition, we studied the effects of hybridization of these symbionts on feeding preference of herbivores and their natural enemies. We used Arizona fescue as the host‐plant, Neotyphodium endophytes as symbionts, the bird cherry–oat aphid as the herbivore and the pink spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
(107 reference statements)
0
12
0
Order By: Relevance
“…By contrast, studies in native grass systems, although fewer in number, have reported higher herbivore abundances on endophyte-infected plants (Jani et al 2010;Faeth and Shochat 2010). However, the effects of endophytes on herbivore performance and communities are highly variable and dependent upon many factors, including soil moisture and nutrients (Saikkonen et al 2006(Saikkonen et al , 2010aSaona et al 2010), plant genotype (Yurkonis et al 2014), types and concentrations of endophyte produced alkaloids (Jani et al 2010), endophyte reproductive strategy (Tintjer and Rudgers 2006), endophyte hybridization (Saari et al 2014), and herbivore identity and diet breadth (Hartley and Gange 2009;Afkhami and Rudgers 2009). In our system, for example, F. rubra is a preferred food source for rabbits and grazing often results in decreased abundance of this grass (Crawley 1990).…”
Section: Alternate Hypotheses Explaining Endophyte Dynamics In the Fieldmentioning
confidence: 85%
“…By contrast, studies in native grass systems, although fewer in number, have reported higher herbivore abundances on endophyte-infected plants (Jani et al 2010;Faeth and Shochat 2010). However, the effects of endophytes on herbivore performance and communities are highly variable and dependent upon many factors, including soil moisture and nutrients (Saikkonen et al 2006(Saikkonen et al , 2010aSaona et al 2010), plant genotype (Yurkonis et al 2014), types and concentrations of endophyte produced alkaloids (Jani et al 2010), endophyte reproductive strategy (Tintjer and Rudgers 2006), endophyte hybridization (Saari et al 2014), and herbivore identity and diet breadth (Hartley and Gange 2009;Afkhami and Rudgers 2009). In our system, for example, F. rubra is a preferred food source for rabbits and grazing often results in decreased abundance of this grass (Crawley 1990).…”
Section: Alternate Hypotheses Explaining Endophyte Dynamics In the Fieldmentioning
confidence: 85%
“…For example, insect species may have individual susceptibility to various alkaloidal compounds (Siegel et al, 1990;Crawford et al, 2010;Schardl et al, 2013). Further complicating the picture is that endophytic alkaloids could be sequestered by the insect herbivore and used as defense against their own natural enemies (Saari et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Correlative and experimental field studies showed that an endophyte from the Cloudcroft population may affect arthropods similar to other Epichloë spp. Infection and its associated alkaloids reduce abundances of arthropod predators or parasitoids, negatively affect generalist herbivores, and provide enemy‐free space for specialized herbivores that are capable of alkaloid detoxification and sequestering for their own defense (Jani et al., ; Faeth & Saari, ; Saari et al., ). Insect bioassays using the generalist herbivore Rhopalosiphum padi (L.) indicate that aphids did not survive on infected plants originating from the Cloudcroft population (Shymanovich et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather there are other factors, such as interactions with herbivores and natural enemies (e.g., Saari et al. ) or relative fitness measures related to plant genotype that dictate the distribution of hybrid infected plants in nature.…”
Section: Discussionmentioning
confidence: 99%